Membangun Usaha Kreatif dan Inovatif Melalui Penerapan Penjualan Donat - Muhammad Sinar Randi; Dinda Salsabila; Faisa Rahma Safira Siregar; Najwa Dwi Aprillia; Putri Amelia (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Building a creative & innovative business is a key strategy for facing increasingly tight market competition. One business model that can be developed using this approach is selling donuts. Donuts, being a culinary favorite among various groups, have huge market potential if managed using this method. the good one. The purpose of this research is to find out how to build a creative and innovative business through the implementation of donut sales. This research method uses a qualitative approach with literature study, by collecting and analyzing several relevant articles and books regarding the donut business. From this research the author found three discussion results, firstly understanding the definition of creative and innovative business, secondly, strategies for building a creative and innovative donut business, thirdly, capital and profits from implementing donut sales.